Effects of Copy Number Variations on Developmental Aspects of Children With Delayed Development - Park, Kee-Boem; Nam, Kyung Eun; Cho, Ah-Ra; Jang, Woori; Kim, Myungshin; Park, Joo Hyun (Annals of rehabilitation medicine, 2019)
To determine effects of copy number variations (CNV) on developmental aspects of children suspected of having delayed development. A retrospective chart review was done for 65 children who underwent array-comparative genomic hybridization after visiting physical medicine & rehabilitation department of outpatient clinic with delayed development as chief complaints. Children were evaluated with Denver Developmental Screening Test II (DDST-II), Sequenced Language Scale for Infants (SELSI), or Preschool Receptive-Expressive Language Scale (PRES). A Mann-Whitney U test was conducted to determine statistical differences of developmental quotient (DQ), receptive language quotient (RLQ), and expressive language quotient (ELQ) between children with CNV (CNV(+) group, n=16) and children without CNV (CNV(-) group, n=37). Of these subjects, the average age was 35.1 months (mean age, 35.1±24.2 months). Sixteen (30.2%) patients had copy number variations. In the CNV(+) group, 14 children underwent DDST-II. In the CNV(-) group, 29 children underwent DDSTII. Among variables, gross motor scale was significantly (p=0.038) lower in the CNV(+) group compared with the CNV(-) group. In the CNV(+) group, 5 children underwent either SELSI or PRES. In the CNV(-) group, 27 children underwent above language assessment examination. Both RLQ and ELQ were similar between the two groups. The gross motor domain in DQ was significantly lower in children with CNV compared to that in children without CNV. This result suggests that additional genetic factors contribute to this variability. Active detection of genomic imbalance could play a vital role when prominent gross motor delay is presented in children with delayed development.